Alternative fuels co-fired with natural gas in the pre-calciner of a cement plant: Energy and material flows. (1st July 2021) - Nhuchhen, Daya R.; Sit, Song P.; Layzell, David B.
Highlights: Materials and energy flows in the clinker production process were reviewed. AF co-firing in an NG-fired cement plant was examined using a thermal model. Increasing [O2 ] in flue gas from 1% to 3% increases thermal energy intensity by 13%. Co-firing C-neutral wood dust at 3% [O2 ] lowers GHG emissions by 43 kgCO2 /t clinker. The regression equation provides a quick estimation of the thermal energy intensity. Abstract: Cement-making is an energy-intensive industrial process that contributes 8% of the global CO2 emissions. This study develops a thermal energy flow model (TEF) for 4200 tonnes of clinker per day, a natural gas-fired cement plant in which 50% of the pre-calciner energy requirements can be supplied by alternative fuels (AF) including biomass, plastics, etc. The TEF shows that the lower heating value (LHV dry), oxygen content (dry basis) and moisture content of the AF, as well as the flue gas oxygen concentration [O2 ] needed for complete combustion, affect the thermal energy intensity (TEI) and total air demand (AD). Compared to the reference system fueled by natural gas (NG) that burns completely at 1% [O2 ] in flue gas, all AFs require more total air and thermal energy demand, especially when the solid AFs need a higher [O2 ] in the flue gas (typically 3%) to ensure complete combustion. Due to the higher carbon (C) intensity, co-firing AFs could increase the total CO2 emissions by 1% to 18%. For the wood dust with 100% biogenic C, 50% NG replacement in pre-calciner could avoid 55.5 and 43.1 kgCO2 /t clinker at 1% and 3% [O2 ] in flue gas respectively, an equivalent of 7.5% and 5.8% decrease in total GHG emissions relative to the reference case. Results of the TEF model from 24 diverse AFs were used to generate regressions that link fuel properties and flue gas oxygen requirement with TEI, making it possible to compare highly diverse AFs for their likely performance in the clinker-making.